PhD Students’ Perceptions Regarding the Utilization of AI tools in Academic Research Writing (Comprehensive Journal of Science, 2025)
The new wave of technology has increased the reliance on artificial intelligence (AI) tools in diverse contexts, particularly in academic writing. Postgraduate students increasingly use AI to enhance accuracy and quality in their work, as Ph.D. programs require critical thinking and argumentative writing. Tools such as Grammarly, Perplexity, and Gemini are widely employed for paraphrasing, summarizing, and generating ideas. Yet, ethical guidelines and regulations among Libyan postgraduate students remain unexplored. This paper investigates Libyan Ph.D. students’ perceptions of AI applications to support their academic research writing. Guided by the mixed method approach, the study employed quantitative measures alongside semi-structured interviews with six Ph.D. candidates at the English Department, Benghazi University. The findings revealed growing reliance and acceptance of AI tools among doctoral students. However, the results emphasized students’ concerns regarding ethical use and the lack of institutional regulations. In response, the current paper proposes a framework for responsible AI use in doctoral research, calling for urgent institutional policies, context-specific application, and ethical guidelines. This work contributes to the existing knowledge on AI academic use and highlights the urgent need for a well-established AI integration policy in Libya’s doctoral education system.
Keywords: AI (Artificial Intelligence), guidelines, academic writing.